Protective effects of low molecular weight chondroitin sulfate on amyloid beta (Aβ)-induced damage in vitro and in vivo. (1st October 2015) - Zhang, Q.; Li, J.; Liu, C.; Song, C.; Li, P.; Yin, F.; Xiao, Y.; Li, J.; Jiang, W.; Zong, A.; Zhang, X.; Wang, F.
Graphical abstract: Highlights: LMWCS protected nerve injury induced by amyloid beta (Aβ) in vitro and in vivo . LMWCS reduced cellular damage in vitro and improved the memory loss of mice in vivo . LMWCS blocked Aβ-associated neurotoxicity by inhibiting apoptosis. Abstract: In the present study, we investigated the effects of low molecular weight chondroitin sulfate (LMWCS) on amyloid beta (Aβ)-induced neurotoxicity in vitro and in vivo . The in vitro results showed that LMWCS blocked Aβ25 – 35 -induced cell viability loss and apoptosis, decreased intracellular calcium concentration, reactive oxygen species (ROS) levels, the mitochondrial membrane potential (MMP) depolarization, and the protein expression of Caspase-3. During in vivo experiments, LMWCS improved the cognitive impairment induced by Aβ1–40, increased the level of choline acetyltransferase (ChAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), and decreased the level of malondialdehyde (MDA) and acetylcholinesterase (AChE) in the mouse brain. Moreover, LMWCS decreased the density of pyramidal cells of CA1 regions, and suppressed the protein expression of Bax/Bcl-2 and Caspase-3, -9 in the hippocampus of mice. In conclusion, LMWCS possessed neuroprotective properties against toxic effects induced by Aβ peptides both in vitro and in vivo, which might be related to anti-apoptotic activity. LMWCS might be a useful preventive and therapeutic compound for Alzheimer's disease.